Eksplorasi Pengalaman Guru PAI dalam Pembelajaran Interaktif Berbasis Penguatan Nilai Sosial dan Moral - Lutfi Muhammad Fauzi; Munawar Rahmat; M Rindu Fajar Islamy (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
This study aims to explore the experiences of Islamic Religious Education (PAI) teachers in implementing interactive learning based on the reinforcement of social and moral values at junior high schools (SMP) in Bandung. The study employed a mixed-methods approach with a sequential explanatory design: quantitative data were collected via a 34 item self-assessment questionnaire from nine PAI teachers selected through purposive sampling, analyzed descriptively, and then explored in depth through five open-ended written questions analyzed thematically and reflectively following Braun and Clarke’s procedures. The results indicate that teachers’ orientation toward interactive teaching practices falls into the “very high” category, marked by a shift in the teacher’s role from sole information provider to facilitator of dialogue. The reinforcement of social values serves as a gateway for students to internalize moral values. Overall implementation barriers were classified as low; however, time constraints remained prominent and were exacerbated by layered value dissonance: external, structural, and interpersonal. The success of interactive learning depends on a collective support ecosystem involving collegiality within the MGMP, partnerships with parents, and teachers’ personal readiness. Given the small sample size, these findings are exploratory and contextual in nature and should be interpreted as preliminary trends. This study contributes to the literature on Islamic education by identifying the reinforcement of social and moral values as a dimension that can be empirically mapped.